2007
DOI: 10.1002/sdr.361
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a care innovation: telecare

Abstract: The provision of health and social care for an increasing elderly population is a challenge facing many societies. Telecare, the delivery of health and social care to individuals within the home or wider community, with the support of information and communication technologies, has been advocated as an approach to reduce the rise in the number of elderly people in institutional care and to contain costs. A dynamic model is required to understand the systemic impact of telecare implementation over time. The pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 11 publications
(15 reference statements)
1
37
0
1
Order By: Relevance
“…Research on how technology affects carers has shown that technology can benefit them through greater 'peace of mind' and lowered stress, by creating opportunities for carers to take breaks or engage with wider social networks and may enhance some caring relationships (Magnusson et al, 2005;AKTIVE Consortium, 2013). Some older people have been shown to value assistive technology for the improved sense of security it can provide, and there are known ways in which assistive technology can support the independence and autonomy of disabled or older people, including those with cognitive, sensory, mobility or other impairments (Bayer et al, 2007;Beale et al, 2009;Hamblin et al, 2016). However recent studies suggest the potential and claimed benefits of care technologies are not yet fully realised, especially when care arrangements are complex, with different family members, workers, neighbours or friends involved in a frail older person's support (Schmidt et al, 2011).…”
Section: Technology and Carementioning
confidence: 99%
“…Research on how technology affects carers has shown that technology can benefit them through greater 'peace of mind' and lowered stress, by creating opportunities for carers to take breaks or engage with wider social networks and may enhance some caring relationships (Magnusson et al, 2005;AKTIVE Consortium, 2013). Some older people have been shown to value assistive technology for the improved sense of security it can provide, and there are known ways in which assistive technology can support the independence and autonomy of disabled or older people, including those with cognitive, sensory, mobility or other impairments (Bayer et al, 2007;Beale et al, 2009;Hamblin et al, 2016). However recent studies suggest the potential and claimed benefits of care technologies are not yet fully realised, especially when care arrangements are complex, with different family members, workers, neighbours or friends involved in a frail older person's support (Schmidt et al, 2011).…”
Section: Technology and Carementioning
confidence: 99%
“…The stated objective is to support a growing proportion of older people to live independently in their own home for longer, by preventing unnecessary hospital admissions, permitting earlier discharges and reducing the numbers admitted to residential care [1]. Less often stated, but perhaps of greater concern in terms of its implications for the end users of support services, is the need to control the escalating costs of healthcare for those in later life.Evidence is gradually accumulating that shows the efficacy of telecare in reducing hospital admissions and unblocking beds [6,24]. Early trials suggest that it may be efficacious in managing chronic disease, by harnessing ICT to deliver continuous care to people in their own homes [9,19].…”
mentioning
confidence: 99%
“…Evidence is gradually accumulating that shows the efficacy of telecare in reducing hospital admissions and unblocking beds [6,24]. Early trials suggest that it may be efficacious in managing chronic disease, by harnessing ICT to deliver continuous care to people in their own homes [9,19].…”
mentioning
confidence: 99%
“…Two-way visual contact through webcams and television monitors is also available, though less widely, and relatively inexpensively. This enables family or paid support workers to 'look in' on an older person and their home without travelling (Bayer et al 2007;Bowes and McColgan 2006). If older people are comfortable with computers, virtual visiting is cheap and easily accessed-no more difficult to obtain than a Skype account-and there are virtual visiting systems simpler than Skype which operate using local broadband networks.…”
Section: Robots 'Presence' and The Requirements Of Carementioning
confidence: 99%